Introducing Environmental Taxes in Tanzania: An Empirical Analysis - Chindengwike, James (Journal of Sustainable Economics, 2025)
Environmental tax is very crucial to support the government revenue in both developing and developed countries. The aim of this paper is assess the important of introducing environmental taxes in Tanzania. The empirical analysis was used from 13 research articles and different reports from various international institutions database such as International Momentary Fund (IMF), World Bank (WB) and African development bank and Tanzania Revenue Authority (TRA) from semantic scholar, google scholar and research gate. The study found that introducing of environmental taxes are very important since source of revenue, improve the environmental, environmental taxes provide a continued incentive to cut emissions at all levels. The study recommends that the effective environmental taxes should need to be proportionate to the harm done to the environment, the flexibility of environmental taxes to offer comparable abatement incentives on each unit of pollution is one of its benefits, the tax rate need to be proportionate to the harm done to the environment and reflecting environmental damage.